Designing in-depth semi-structured interviews for revealing meaning reconstruction after loss. Issue 2 (7th February 2021) - Mahat-Shamir, Michal; Neimeyer, Robert A.; Pitcho-Prelorentzos, Shani
Abstract: The recent upsurge in the use of qualitative empirical studies, aiming to provide a deeper understanding of human reactions to loss, requires a methodological account of how to conduct better qualitative research with regard to data collection. This paper offers six general interview guidelines aimed at assisting researchers to achieve quality interviews in qualitative bereavement studies, based on the theoretical framework of meaning (re)construction in loss.